Kompetensi Kepribadian Guru dalam Membentuk Karakter Peserta Didik - Abu A’la Al Maududi; Nur Fadillah Dalimunthe; Malikul Sholeh As Salim; Khairun Nisa (Lembaga Pengembangan Kinerja Dosen, 2026)
This study explores the profound impact of teacher personality competence on student character formation through a descriptive narrative lens grounded in the sociology of education. Education is not merely a technical transfer of knowledge but a complex social process where the teacher acts as a pivotal moral agent and role model. By synthesizing classical sociological paradigms—Functionalism, Conflict Theory, and Symbolic Interactionism—with contemporary empirical evidence, this article argues that a teacher's personality is a dynamic social construct that shapes the